Educação Básica e sua importância na construção da identidade étnico-racial do discente, na perspectiva da Lei 10.639/03: - Melo, Joelma Araújo Borges de (Universidade Federal do Tocantins, 2023)
The present research sought to show the importance of basic education for the ethnic-racial formation of the student in building your own identity without fear of race/color. A study about an issue that emerges with the law n. 10,639/03 that is treated of the mandatory teaching of history and culture of the African-Brazilian and African schools, then amended by law no. 11,645/08, which also includes the mandatory teaching of history and indigenous culture, because you can't enhance a culture at the expense of another. Reflecting about the demands and national curriculum guidelines for implementation of this law, having as core the formal curriculum and the practiced curriculum with the propose of realizinghowhappens to